A cidade das aquarelas: o Rio de Janeiro nos registros de Jean-Baptiste Debret - Domingues, Bruno Willian Brandão (2018)
In order to analyze how foreign travelers reported and portrayed Brazil, the following research had been devoted to Jean-Baptiste Debret's analyzes of iconographic and written sources. Debret's artistic history at the court of Napoleon Bonaparte had greatly influenced his choice as a historical painter of the court of D. João VI and later of D. Pedro I after his coming to Brazil as part of the "Mission" Artistica Francesa, closely following all the events of the monarchy in the tropics. Through the study of his works, we realized that his role was not only as a historical painter, but also a picturesque painter, with a vast collection of representations of the daily life and culture of the Brazilian people, especially in the city of Rio de Janeiro